Pengembangan Media Powerpoint Interaktif Berbasis Android untuk Pembelajaran Matematika di Sekolah Dasar pada Masa Pandemi Covid-19 - Arfi Nofianggy Hidayat; Fredy Fredy; Ratna Purwanty (Faculty of Teacher Training and Education, Musamus University, 2021)
Distance learning is currently implemented by several schools. It has some problems in learning media that used by students in their home. This research aims to a product in the form of interactive PowerPoint media for mathematics learning of valid and practical. This study used a modified 4D model development research method, namely define, design, and development. The data collection instrument used a questionnaire. Questionnaire was given to the expert validators and media experts to assess the validity of the media, and student response questionnaires to see the practicality of the media. Subjects were grade IV students of MI Integral Al-Hikmah Hidayatullah Merauke. The results showed the material expert's assessment of the product developed before revision had an average score of 51,5 in the good category. After being revised, the average increased to 66 in the very good category. In contrast to the results of the media expert's assessment. Before being revised, the media expert's assessment had an average score of 61,5 with a medium category. Then, after being revised by the experts, the average value increased to 108 in the very good category. Grade IV students' assessment has a practicality percentage of 91%. The products developed have met the standards of assessment from experts’ judgment and students.